Estimación de la degradabilidad efectiva en el rumen mediante métodos numéricos - Correa, Héctor J. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary In order to develop efficient feeding programs for ruminants, it is required to make a correct estimation of the effective ruminal degradability (ED) of the nutritional fractions. The classical calculation of ED (DEb=bKd/(Kd+Kp)) lacks precision, because it erroneously assumes that the kinetic constants Kd and Kp represent fermentation velocity and velocity of passage through the rumen, respectively. In reality, Kd actually represents the constant relationship between acceleration and degradation velocity, while Kp represents the relationship between acceleration and velocity of passage. Considering this information, a new proposal is being presented that takes into account the correct mathematical interpretation of the ruminal degradation and passage kinetics.